THE INFLUENCE OF EXCHANGE RATE, INFLATION RATE, DEBT TO EQUITY RATIO, EARNINGS PER SHARE, AND RETURN ON ASSETS ON STOCK RETURN OF FOOD AND BEVERAGE COMPANIES LISTED ON INDONESIA STOCK EXCHANGE (IDX) - Zuhri, Mohammad Nanda Anugrah (Jurnal Ilmiah Mahasiswa FEB, 2021)
This study aims to determine the effect of exchange rate, inflation rate, debt to equity ratio, earning per share, and return on assets on stock returns of food and beverages companies listed on the Indonesian stock exchange. This research is a causal research which aims to prove the causality relationship between variables. The number of samples in this study were 11 companies from a population of 25 companies. This study uses secondary data obtained from annual reports of companies in the Food and Beverage sector from 2014 to 2018, stock returns of Food and Beverage companies based on stock closing prices from the Indonesia Stock Exchange (IDX) Annual Report 2014 to 2019, Consumer Price Index from Central Bureau of Statistics for 2014 2018, and JISDOR USD-IDR Reference Rate from Bank Indonesia during 2014-2018. The data analysis technique used in this study is multiple linear regression using SPSS. The results of this study indicate that the exchange rate and inflation rate do not have a significant effect on stock returns. Meanwhile, debt to equity ratio and earnings per share have a significant effect on stock returns, while the return on assets do not have a significant effect on stock returns.Keywords: Exchange Rate, Inflation Rate, Debt to Equity Ratio, Earnings per Share, Return on Assets, Stock Return